2014
DOI: 10.1002/chem.201304462
|View full text |Cite
|
Sign up to set email alerts
|

Stabilisation of 2,6‐Diarylpyridinium Cation by Through‐Space Polar–π Interactions

Abstract: The through-space polar-π interactions between pyridinium ion and the adjacent aromatic rings in 2,6-diarylpyridines affect the pKa values. Hammett analysis illustrates that the basicity of pyridines correlates well with the sigma values of the substituents at the para position of the flanking aryl rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 34 publications
5
33
1
Order By: Relevance
“…In this regard, virtually the same ρ value was observed for the series of analogous 2,6-diarylpyridines. 5 The presence of the electron-donating groups (e.g., OMe) leads to a weaker acidity of the anilinium ion (and stronger basicity of the aniline); the observation that could be attributed to through-space stabilization of anilinium ion by the electron-rich aromatic rings. Accordingly, the presence of the electron-withdrawing groups (e.g., CF 3 ) makes the anilinium ion a significantly stronger acid.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, virtually the same ρ value was observed for the series of analogous 2,6-diarylpyridines. 5 The presence of the electron-donating groups (e.g., OMe) leads to a weaker acidity of the anilinium ion (and stronger basicity of the aniline); the observation that could be attributed to through-space stabilization of anilinium ion by the electron-rich aromatic rings. Accordingly, the presence of the electron-withdrawing groups (e.g., CF 3 ) makes the anilinium ion a significantly stronger acid.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of solvation was simulated by means of the Conductor like Screening Model (COSMO) of solvation as implemented in ADF. The approach has been benchmarked against highly correlated post-Hartree–Fock methods and experimental data and was found to work reliably 61 62 63 .…”
Section: Methodsmentioning
confidence: 99%
“…The observed slope provided the ρ value of +1.1, which is essentially the same as the one found for 2,6diarylanilines and 2,6-diarylpyridines. 21,22 These results indicate that para-substituted donating groups (e.g. OMe, Me) make the neighboring flanking aromatic rings more electron-rich, thus leading to significant stabilization of 2,6-diarylphenols, as manifested by higher pKa values (i.e.…”
mentioning
confidence: 97%
“…We conceived that the arrangement of two flanking aromatic rings around the central phenolic 3 ring in 2,6-diarylphenols enables detailed experimental and computational examinations of proposed through-space OH-π interactions at the unprecedented level of molecular detail. Physical-organic studies on the most related 2,6-diarylcarboxylic acids, 20 2,6-diarylpyridines, 21 and 2,6-diarylanilines 22 revealed that the linear trends in acidities of such systems are a result of through-space effects ( Figure 1). We hypothesized that the two neighboring flanking aromatic rings of 2,6-diarylphenols do not stabilize the protonated form of phenol via through-bond interactions, but rather via through-space OH-π interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation